Re-Imagining Punishment: An Exercise in “Intersectional Criminal Justice” - Maya Pagni Barak (Laws, 2014)
Over the last 40 years a number of scholars have called upon fellow criminologists to rethink the field’s priorities and methods, as well as the American criminal justice system and current punishment practices. Drawing on alternative criminologies, including constitutive and peacemaking criminologies, as well as the practice of reintegrative shaming, this paper presents a new model of criminal justice that combines aspects of adversarial, restorative, social, and transformative justice frameworks. The resulting “intersectional criminal justice” offers a holistic harm-reduction model that moves the focus of our criminal justice system away from “rough justice” and towards collective restorative healing and positive social change.